Price Gouging or Market Forces? Fairness Perceptions of Price Hikes in the Pandemic - Snir. Avichai; Daniel Levy; Dudi Levy; Haipeng Allan Chen (ZBW - Leibniz Information Centre for Economics, 2024)
We report the results of surveys we conducted in the US and Israel in 2020, a time when many prices increased following the spread of the COVID-19 pandemic. To assess respondents' perceptions of price increases, we focus on goods whose prices have increased during the pandemic, including some essential goods. Consistent with the principle of dual entitlement, we find that respondents perceive price increases as more acceptable if they are due to cost shocks than if they are due to demand shocks. However, we also find large differences across the two populations, as well as across goods.
Keywords: E31; E70; D90; M31; 330; Fairness Perceptions; Price Increases; The Pandemic; Dual Entitlement; Consumer Antagonism